If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + x = -2(1 + -7x) 37 + x = (1 * -2 + -7x * -2) 37 + x = (-2 + 14x) Solving 37 + x = -2 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 37 + x + -14x = -2 + 14x + -14x Combine like terms: x + -14x = -13x 37 + -13x = -2 + 14x + -14x Combine like terms: 14x + -14x = 0 37 + -13x = -2 + 0 37 + -13x = -2 Add '-37' to each side of the equation. 37 + -37 + -13x = -2 + -37 Combine like terms: 37 + -37 = 0 0 + -13x = -2 + -37 -13x = -2 + -37 Combine like terms: -2 + -37 = -39 -13x = -39 Divide each side by '-13'. x = 3 Simplifying x = 3
| 3x+7y=176 | | -4k-44k=36 | | .05x+15=y | | (a-7)(2a+9)= | | 1u^2-4u-45=0 | | 2x^2+102=-60 | | 3X+4=22whatisX | | 10r=90 | | U^2-4u-45=0 | | -8(-2+2x)+8=-40 | | 72=4y+12 | | f(x)=-0.0009x^2+0.2088x | | 6h+13=5 | | m+123+29=180 | | -3-(-56)= | | -d^2+d=-6 | | f=3(22) | | -2+2.3w=10 | | 4(a+3)=6a+12 | | m+123+23=180 | | 12x+11+-4= | | 266=-7(-7x+11) | | x+15=7x-9 | | 4n=944 | | 4=x/13+1 | | 7x+3y=37 | | 4a+3=6a+12 | | 23=-1+6(3x-2) | | 7n-4n+11n= | | 4x+21=5x+10 | | 8(3)=v | | 11c+21=-24 |